Four new subspecies of butterflies (Lepidoptera, Papilionoidea) from Phu Quoc Island, southern Vietnam - Tamamitsu, Saito; Lien, Vu Van (Zootaxa, 2023)
We describe and illustrate four new subspecies of Papilionoidea butterflies which were collected from Phu Quoc Island, Kien Giang province, southern Vietnam between 2006 and 2017. These are papilionid Graphium antiphates matsui T. Saito & Vu subspec. nov.; Nymphalidae: Tanaecia julii duc T. Saito & Vu, subspec. nov.; Cynitia lepidea phuquoca T. Saito & Vu, subspec. nov.; and Bassarona teuta anh T. Saito & Vu, subspec. nov.